Improved power clean performance with the hook-grip is not due to altered force-time or horizontal bar-path characteristics. Issue 2 (17th January 2022) - Oranchuk, Dustin J.; Harbour, Eric T.; Lindsay, Riki S.; Storey, Adam G.; Drinkwater, Eric J.
ABSTRACT: he underlying biomechanical benefits of hook-grip (HG) over conventional closed-grip (CG) remain unclear. This study compared bar-path kinematics and force-time variables of the power clean (PC) performed with HG or CG. We also aimed to compared kinetic changes measured by force platform versus linear position transducer (LPT). Eleven well-trained men volunteered. Following a familiarisation session, HG, and CG 1RM conditions, were randomly completed seven days apart. System kinetics and barbell kinematics were recorded via synchronized force platform+LPT system and two-dimensional motion-capture. Statistical parametric mapping (SPM), analysis of variance, and standardised differences were utilised. The SPM cut-offs were determined via novel combination of force and displacement. No between-condition differences in normalised force-time variables of the pull or catch were detected. The first and second pull duration was similar between conditions (ES = 0.04–0.38). Conversely, catch and total PC durations were shorter at 80–95% (ES = 0.26–0.75), with the weightless phase more prolonged at 95% and 100% (ES = 0.54–0.76) with HG compared to CG. Improved timing of the turnover and catch phases appears to be the primary difference between HG and CG performance. Thus, grip type is possibly irrelevant to non-weightlifting athletes when performing submaximal catch-less derivatives..